2022
DOI: 10.1021/acs.orglett.2c00519
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Ketones via Chemoselective Suzuki–Miyaura Cross-Coupling of Acyl Chlorides

Abstract: The direct synthesis of ketones via acyl Suzuki− Miyaura cross-coupling of widely available acyl chlorides is a central transformation in organic synthesis. Herein, we report the first mechanochemical solvent-free method for highly chemoselective synthesis of ketones from acyl chlorides and boronic acids. This acylation reaction is conducted in the solid state, in the absence of potentially harmful solvents, for a short reaction time and shows excellent selectivity for C(acyl)−Cl bond cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…7 The organic synthesis reaction promoted by a mechanical force often has the advantages of high reaction efficiency, short reaction time, less or no solvent to increase the reactivity of insoluble reactants, no heating and simple post-treatment. 8 Classical organic reactions including the Suzuki–Miyaura reaction, 9 Buchwald–Hartwig reaction 10 and Heck reaction 11 facilitated by mechanical forces have been realized. In addition, mechanochemistry could also change the product selectivity 12 and even trigger new reactions.…”
Section: Introductionmentioning
confidence: 99%
“…7 The organic synthesis reaction promoted by a mechanical force often has the advantages of high reaction efficiency, short reaction time, less or no solvent to increase the reactivity of insoluble reactants, no heating and simple post-treatment. 8 Classical organic reactions including the Suzuki–Miyaura reaction, 9 Buchwald–Hartwig reaction 10 and Heck reaction 11 facilitated by mechanical forces have been realized. In addition, mechanochemistry could also change the product selectivity 12 and even trigger new reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Szostak et al . reported a chemoselective Suzuki‐Miyaura method to obtain ketones from acyl chlorides under ball‐milling conditions [47] . Following the work of Mack et al .…”
Section: Resultsmentioning
confidence: 99%
“…[46] Recently, Szostak et al reported a chemoselective Suzuki-Miyaura method to obtain ketones from acyl chlorides under ball-milling conditions. [47] Following the work of Mack et al on the solvent-free Sonogashira coupling, [48] Stolle et al reported a copper-free variant of the method using DABCO, resulting in high yields in much shorter reaction times. [49] Furthermore, in recent works, Browne et al described Ni-catalyzed processes [50,51] and Ito and Kubota et al reported a study on solid-state cross-coupling of insoluble aryl halides [52] and published very comprehensive and detailed works on mechanochemical CÀ N cross-coupling methods.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various treatments, there has been considerable research on semiconductor photocatalysts that have the ability to perform reactions under visible light. [4][5][6][7][8][9][10] TiO 2 has been frequently investigated, and it has become the most promising photocatalyst to use in organic reactions due to its high efficiency, high photocatalytic activity, nanotoxicity, cost-effectiveness, and chemical stability. [11][12][13][14][15] Nevertheless, because of the wide band gap of pristine titanium dioxide (TiO 2 ), it is inefficient for carrying out reactions under visible light.…”
Section: Introductionmentioning
confidence: 99%